DETERMINANTS OF CARBON EMISSION DISCLOSURE IN ENERGY COMPANIES IN INDONESIA - Wiguna, Roy Saputra; Stephanus, Daniel Sugama; Pratama, Bagas Brian (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2025)
ABSTRACTBy 2060, Indonesia has a goal of achieving net zero emissions. Indonesia has raised its carbon emission reduction target in the contribution statement determined nationally by the Nationally Determined Contribution and as a step to support the achievement of net zero emissions, the President of the Republic of Indonesia Joko Widodo officially launched IDXCarbon. This research is quantitative research that uses legitimacy theory and stakeholder theory. The focus of this research is on the energy producing industry as the largest contributor to greenhouse gas emissions. This research aims to examine the factors that influence the disclosure of carbon emissions by energy companies in Indonesia. Indonesia's carbon emission disclosure procedures are voluntary or self-driven. The independent variables used include carbon emission intensity, profitability, leverage and environmental performance. The research results show that leverage has a significant negative influence on carbon emission disclosure, while other variables such as carbon emission intensity, profitability and environmental performance have no effect on carbon emission disclosure. The relationship between carbon emission intensity, profitability, leverage and environmental performance and carbon emission disclosure is not always consistent. These factors are not always the primary predictors in a company's decision to report carbon emissions, and it is important to consider the company's specific context and external factors in analyzing carbon emissions disclosures.Keywords: Carbon Emission Disclosure; Environment; Net Zero Emission ABSTRAKPada tahun 2060, Indonesia memiliki tujuan untuk mencapai net zero emission. Indonesia telah menaikkan target pengurangan emisi karbon dalam pernyataan kontribusi yang ditentukan secara nasional oleh Nationally Determined Contribution serta sebagai langkah untuk mendukung pencapaian net zero emission ini Presiden Republik Indonesia Joko Widodo secara resmi meluncurkan IDXCarbon. Penelitian ini menggunakan penelitian kuantitatif menggunakan teori legitimasi dan stakeholder. Fokus penelitian pada industri sektor energi sebagai penyumbang terbesar emisi gas rumah kaca dengan tujuan menguji faktor-faktor yang memengaruhi pengungkapan emisi karbon perusahaan energi di Indonesia. Prosedur pengungkapan emisi karbon Indonesia bersifat sukarela. Variabel independen meliputi carbon emission intensity, profitabilitas, leverage, dan kinerja lingkungan. Hasil penelitian menunjukkan leverage berpengaruh negatif yang signifikan terhadap carbon emission disclosure sedangkan variabel lain yaitu carbon emission intensity, profitabilitas, dan kinerja lingkungan tidak berpengaruh terhadap carbon emission disclosure. Hubungan antara carbon emission intensity, profitabilitas, leverage, dan kinerja lingkungan terhadap pengungkapan emisi karbon tidak selalu konsisten. Faktor-faktor tersebut tidak sepenuhnya menjadi prediktor utama keputusan perusahaan untuk melaporkan emisi karbon dengan penting mempertimbangkan konteks spesifik perusahaan dan faktor eksternal dalam menganalisis pengungkapan emisi karbon.Kata Kunci: Carbon Emission Disclosure; Lingkungan; Net Zero Emission